2018
DOI: 10.3390/min8110475
|View full text |Cite
|
Sign up to set email alerts
|

Rock Sample Surface Preparation Influences Thermal Infrared Spectra

Abstract: High-resolution laboratory-based thermal infrared spectroscopy is an up-and-coming tool in the field of geological remote sensing. Its spatial resolution allows for detailed analyses at centimeter to sub-millimeter scales. However, this increase in resolution creates challenges with sample characteristics, such as grain size, surface roughness, and porosity, which can influence the spectral signature. This research explores the effect of rock sample surface preparation on the thermal infrared spectral signatur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…The spectral structure, relative band magnitudes and wavenumber offsets of reflectance and transmittance features presented in Fig. 4 are consistent with spectra reported by Rost and coworkers 27 and Salisbury and coworkers. 28,29 Figure 5 shows the real and imaginary parts of the refractive index for quartz taken from the measurements of Papova et al 30 The strong resonance peak between 1111.1 and 1052.6 cm À1 is associated with the antisymmetric stretching vibration of Si-O-Si bridges.…”
Section: Resultssupporting
confidence: 89%
“…The spectral structure, relative band magnitudes and wavenumber offsets of reflectance and transmittance features presented in Fig. 4 are consistent with spectra reported by Rost and coworkers 27 and Salisbury and coworkers. 28,29 Figure 5 shows the real and imaginary parts of the refractive index for quartz taken from the measurements of Papova et al 30 The strong resonance peak between 1111.1 and 1052.6 cm À1 is associated with the antisymmetric stretching vibration of Si-O-Si bridges.…”
Section: Resultssupporting
confidence: 89%
“…Generally it is assumed that planetary surfaces are covered with a particulate medium that depending on the particle size and shape influences the reflectance spectra of the observed surface (Hiroi & Peters 1991). However, with increasing spatial resolution of the spectral data the porosity and roughness of the surface material can influence the spectral contrast, spectral shape and the absolute reflectance/emission due to additional volume scattering and cavity effects (Rost et al 2018) and should be taken into account in order to avoid a misinterpretation. In addition, the roughness on scales that cause shadowing effects or small scale self-heating have to be considered when interpreting near-infrared and thermal measurements (Davidsson et al 2009).…”
mentioning
confidence: 99%
“…In this section we give a short description of the characteristics of the two sandstones used for this research, followed by a description of the spectral reflectance measurements and results from Rost et al. (2018, Figure 2) and the transmission measurements and the scanning electron microscopy images obtained for this research. At the end of this section, we present our model.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of laboratory‐based geological spectroscopy, several researchers showed that surface roughness of rocks influences thermal infrared (TIR) spectral signatures, both in spectral shape and in amplitude (Hardgrove et al., 2016; Kirkland et al., 2002, 2003; Osterloo et al., 2012; Rost et al., 2018; Salisbury & Wald, 1992). The shape and amplitude (Figure 1) in thermal infrared (TIR) spectra play a critical role in determining the mineral composition of rock samples and drill cores.…”
Section: Introductionmentioning
confidence: 99%